Wage Differentials, Bargaining Protocols, and Trade Unionism in Mid-Twentieth Century American Labor Markets - John Pencavel (Institute of Labor Economics (IZA), 2020)
Income inequality has been lower in periods when trade unionism has been strong. Using observations on wages by occupation, by geography, and by gender in collective bargaining contracts from the 1940s to the 1970s, patterns in movements of wage differentials are revealed. As wages increased, some contracts maintained relative wage differentials constant, some maintained absolute differences in wages constant, others combined these two patterns, and some did not reveal an obvious pattern. The patterns persisted even as price inflation increased in the 1970s. The dominant pattern implies a reduction in inequality as usually measured.
Keywords: J31; J51; N32; 330; income inequality; wage differentials; bargaining; trade unions